Throwing the diamond hitch - Ursuliak, Emily, 1988- (Brave & brilliant series, 2017)
"The Diamond Hitch uses, as its source material, a travel diary kept by my grandmother Phyllis and her best friend Anne, during their journey through the interior of British Columbia in 1951. The first half of the trip was taken in an 1927 MG Roadster the two friends had bought together. The women (both in their twenties) recount the story of their drive from Victoria, British Columbia to Red Deer, Alberta, whereupon they buy two horses, plus a pack-horse, to carry their supplies so that the two women might then return to Victoria on horseback--a trip that takes several months to complete. Their trip occurs in a time when, by convention, young women are unlikely to be vacationing on their own, let alone riding horses through mountain passes, and living off of their wits, if not the kindness of strangers. My manuscript highlights the poetic moments from this travel diary, often using dialogue and descriptions taken directly from the text, and reframing the travelogue as a poetic account. The poems in the collection vary in style, and they capture the eccentric people and unusual places encountered by the women. The work also seeks to tackle the underlying gender tensions faced by the characters during their travels."--